Analyzing India’s Central Public Health Emergency Laws and Its Impact on India’s Economy: A Comprehensive Study - Preeti Upreti (European Economic Letters (EEL), 2024)
Public health emergencies present complex challenges that require coordinated legal responses and medical interventions to mitigate their impact. This research article explores the dynamic interplay between legal frameworks and medical strategies in addressing such emergencies. By analyzing existing legislation, it investigates the effectiveness of legal tools in facilitating timely and effective medical interventions during crises. The primary legislation that somewhere address the public health emergency in India namely the Epidemic Disease Act, 1897 along with some other acts. This research article conducts a comprehensive study of India’s central public health emergency laws, the impact pandemic like Covid-19 had on the Indian economy, examining their scope, efficacy, and applicability in addressing various health crises. Through an analysis of legislation, case studies, and policy documents, the study evaluates the strengths and weaknesses of existing laws in facilitating timely and effective responses to emergencies. Furthermore, it explores the role of these laws in coordinating medical interventions, ensuring resource allocation, and safeguarding public health during emergencies. By shedding light on the legal landscape of public health in India, this study aims to inform policymakers, health professionals, and stakeholders about areas for improvement and optimization in the country’s preparedness and response mechanisms.